Recognition and control of Mycobacterium tuberculosis-infected cells: from basics to the clinic: a NIAID/WGNV workshop report 2023 - Young, Carly; Mkhonza, Mbali N.; Ogongo, Paul (Frontiers in Tuberculosis, 2023)
Vaccination is crucial for the control of tuberculosis (TB), and safe, more effective, and accessible vaccines against Mycobacterium tuberculosis (Mtb) infection are critically needed to achieve TB control milestones envisioned in the End TB Strategy. TB vaccine research and development faces numerous challenges including, but not limited to, insufficient knowledge of the most informative antigens to prioritize as potential vaccine candidates, lack of defined correlates of protection, and incomplete knowledge of anatomical and cellular locations of the Mtb-infected cell in vivo, among others. To take stock of the progress, challenges, and opportunities in TB vaccine R&D, the Stop TB Partnership Working Group on New TB Vaccines (WGNV), in partnership with the National Institute for Allergy and Infectious Diseases (NIAID) cohosted a two-day virtual workshop on 13-14 June 2023 with experts from all over the world. In this report, we summarize key themes and discussions from the meeting, highlighting progress and gaps in the TB vaccine research.